Quantifying the Exchange Coupling in Linear Copper Porphyrin Oligomers - Richert, S; Kuprov, I; Peeks, M; Suturina, E; Cremers, J; Anderson, H; Timmel, C (Royal Society of Chemistry, 2017)
Linear π-conjugated porphyrin oligomers are of significant current interest due to their potential applications as molecular wires. In this study we investigate electronic communication in linear butadiyne-linked copper porphyrin oligomers by electron paramagnetic resonance (EPR) spectroscopy via measurement of the exchange interaction, J, between the copper(II) centers. The contributions of dipolar and exchange interactions to the frozen solution continuous wave (cw) EPR spectra of the compounds with two or more copper porphyrin units were explicitly accounted for in numerical simulations using a spin Hamiltonian approach. It is demonstrated that a complete numerical simulation of the powder spectrum of a large spin system with a Hamiltonian dimension of 26 244 and beyond can be made feasible by simulating the spectra in the time domain. The exchange coupling in the Cu2 dimer (Cu⋯Cu distance 1.35 nm) is of the order of tens of MHz (Ĥ = −2JS1·S2) and is strongly modulated by low-energy molecular motions such as twisting of the molecule.